PENGARUH PENAMBAHAN KALIUM NITRAT DALAM LARUTAN HARA PADA MEDIA KASCING TERHADAP PERTUMBUHAN SELADA (Lactuca sativa L.) - Hangrie Jemmy Namserna (AGRICA, 2013)
This research was conducted with the aim to find out the effect of the addition of potassium nitrate in lettuce as a medium and critical level of concentration(electrical conductivity)of nutrient solution. Research is organized in the form of a pot experiment. The experimental design used was Complete RandomizedBlock Design (CRBD)) with three replications. The treatment consists of 12 levels of concentrations or nutrient solution electrical conductivity with the addition of potassium nitrate to lettuce plant. The treatment level of concentrations (conductivity) of nutrient is as follows; L0 = 0.00; L1 = 1.25; L2 = 2.50; L3 = 3.75; L4 = 5.00; L5 = 6.25; L6 = 7.50; L7 = 8.75; L8 = 10.00; L9 = 11.25; L10 = 12.50 and L1 = 13, 75 g 100 L-1 water. Value concentrations of electrical conductivity each nutrient solution concentrations are: L0 = 0.06; L1 = 0.26; L2 = 0.46; L3 = 0.66; L4 = 0.86; L5 = 1.06; L6 = 1.26; L7 = 1,46; L8 = 1.66; L9 = 1,86; L10 = 2.06 and L1 = 2.26. dS m-1. The result of the experiment showed that addition of KNO3 highly significant effect on the increase in fresh weight and dry weight of shoot per plant. Fresh weight and oven-dry weight of shoot per plant was significantly increased in a quadratic with increasing concentrations of KNO3are optimum for growth of plant shoot weight were at 12.23 g in 100/of water on electrical conductivity equivalent to 2.01 dS.m-1. The addition of concentration of KNO3to nutrient solution does not affect on N and other nutrient solution on shoot tissue of lettuce plant but the concentrations of P and K in plant shoot tissue were significantly increased linearly with the provision of KNO3.